2012
DOI: 10.21608/jpp.2012.84990
|View full text |Cite
|
Sign up to set email alerts
|

Performance Study of Some Sugar Beet Varieties Under Sowing and Harvesting Dates.

Abstract: Two field experiments were carried out Sakha Agricultural Research Station, Kafr El-Sheikh Governrate, during 2009/2010 and 2010/2011 seasons to evaluate three sugar beet varieties (Kawemira, Carolla and Farida) under two sowing dates (15 th October and 15 th November), and two harvesting dates (180 and 210 days from sowing date). Results can be summarize as the following: 1. Sowing sugar beet on 15 th Oct. attained the highest values of root length and diameter, root and top fresh weight/plant, sucrose %, Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
3
1
0
Order By: Relevance
“…Gobarah et al (2019) reported that planting of sugar beet during October produced the highest yields of root and sugar, in addition to quality traits in terms of sucrose, purity% and recoverable sugar. These finding are in line with those obtained by Aly (2012), El-Mansoub & Mohamed (2014, and Gobarah et al (2019).…”
Section: Sowing Datessupporting
confidence: 93%
“…Gobarah et al (2019) reported that planting of sugar beet during October produced the highest yields of root and sugar, in addition to quality traits in terms of sucrose, purity% and recoverable sugar. These finding are in line with those obtained by Aly (2012), El-Mansoub & Mohamed (2014, and Gobarah et al (2019).…”
Section: Sowing Datessupporting
confidence: 93%
“…A significant variation of beet girth was observed in response to date of harvesting ( 3). Similar result was reported by Aly (2012) who showed that delay harvesting of some sugar beet varieties influenced the beet girth.…”
Section: Beet Girthsupporting
confidence: 89%
“…(Paul et al, 2018a;Paul et al, 2018b;Bairagi et al, 2013 andIslam et al, 2012 3). Delay harvesting enhanced beet length that was reported by Aly (2012).…”
Section: Beet Lengthsupporting
confidence: 51%
“…Aly, et al (2011) and Aly, et al (2012) indicated that sugar beet varieties differed significantly in all studies traits, Kawemira variety surpassed all tested varieties in root and sugar yields/fed, while, LP12 and Demapoly had the highest value for sucrose, extraction sugar and extractability percentages. Ahmed et al (2017) and Aly (2012) cleared that sugar beet varieties differed significantly in root and sugar yields/fed. as well as sucrose, purity, impurities percentages.…”
Section: Introductionmentioning
confidence: 97%